Adult learners’ motivation and self-determination towards independent piano learning through mobile application / Teoh Cherylyn - Teoh , Cherylyn (2020)
This study examined the motivating factors and self-determined behaviours of adult learners in independent piano learning through a piano learning app. It employed the narrative inquiry method to gather stories and detailed experiences from the participants through participant interviews, participant journals and self-reflexivity of the researcher. Five working adults from the Klang Valley were recruited to take part in this study and each had a different motivation for piano learning. The unique scenario of this study challenged the adult participants’ motivation in piano learning and presented different challenges faced in self-determined learning. The piano learning app also presented different perceptions towards self-directed learning with apps. The findings of the study found that adult motivation for learning is a result of self-actualization and that self determined learning is challenging for adult learners in terms of human agency. The findings also indicated some success and pitfalls of self-directed learning with apps.